2010
DOI: 10.1371/journal.pone.0010631
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Genetic Diversity of HCV among HIV-1 Infected People from Various High-Risk Groups in China

Abstract: BackgroundCo-infection with HIV-1 and HCV is a significant global public health problem and a major consideration for anti-HIV-1 treatment. HCV infection among HIV-1 positive people who are eligible for the newly launched nationwide anti-HIV-1 treatment program in China has not been well characterized.MethodologyA nationwide survey of HIV-1 positive injection drug uses (IDU), former paid blood donors (FBD), and sexually transmitted cases from multiple provinces including the four most affected provinces in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 34 publications
10
43
3
Order By: Relevance
“…High HCV prevalence and co-infection rate with HIV were observed previously among IDUs in some areas of China [4,12,16,18,20,28,30]. Here, we found that HCV prevalence were 81.6 and 69.9% among IDUs and all drug users in Zhenjiang, Jiangsu (Table 1), respectively, slightly lower than 88.5 and 75.5% in other neighbor cities of Jiangsu, respectively [5].…”
Section: Discussionsupporting
confidence: 59%
“…High HCV prevalence and co-infection rate with HIV were observed previously among IDUs in some areas of China [4,12,16,18,20,28,30]. Here, we found that HCV prevalence were 81.6 and 69.9% among IDUs and all drug users in Zhenjiang, Jiangsu (Table 1), respectively, slightly lower than 88.5 and 75.5% in other neighbor cities of Jiangsu, respectively [5].…”
Section: Discussionsupporting
confidence: 59%
“…Co-circulation of more than 6 HCV subtypes among IDUs were reported previously in Yunnan and Guangxi provinces, 3,5,12 and Zhenjiang city of Jiangsu province. 6 Because of special geographic location, Yunnan and Guangxi serve as important transfer stations for drug trafficking from heroine-producing areas (Golden Triangle region) to China and neighboring countries, and play crucial roles in HIV-1 and HCV transmissions via drug trafficking routes, 2,4,26,27 which result in the mixing multiple HIV-1 and HCV subtypes.…”
Section: Discussionmentioning
confidence: 62%
“…2 High prevalence of HCV and HIV-1 co-infection have been reported among IDUs in China. 5,12,13 Among IDUs, extensive HIV-1 intersubtype recombinants have been detected, 14,15 whereas very few HCV intersubtype recombinants were identified. 16 Up to now, only 2k/1b, 1b/1a, 1a/1c, 2/6, 2b/1b, and 2/5 recombinants have been identified in HCV, [17][18][19][20][21][22][23][24] and no recombinant was detected in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the HCV incidence increased in repeat donors, primarily among 50 years old and older white donors (corresponding to the aging prevalent HCV observed in NHANES) [25•]. As a reminder of the importance of a volunteer, nonremunerated donor system, 93% of former paid blood donors in China had HCV infection [26].…”
Section: Blood Transfusionmentioning
confidence: 99%